Affinity Biosensors Techniques and Protocols - Rogers, Kim.; Rogers, Kim.; Mulchandani, Ashok.; Mulchandani, Ashok. (Methods in Biotechnology,, 1998)
Affinity Biosensors: Protocols and Techniques is a major new work that describes how affinity biosensors are developed, constructed, and applied across the widest range of biological research. Here, scientists long-experienced with the construction and evaluation of these biosensors detail their most successful techniques and applications. The methods include protocols for affinity biosensors based on optical, electrochemical, thermal acoustic, and plasmon resonance techniques involving the use of antibodies, receptor, nucleic acids, liposomes, and eukaryotic cells. All the techniques are time-tested and sufficiently detailed to ensure robust and easily reproducible results. A companion volume, Enzyme and Microbial Biosensors: Protocols and Techniques, by Mulchandani & Rogers, concentrates on enzyme-biosensors based on potentiometric, amperometric, conductimetric, optical, and thermal transducers, as well as microbial biosensors based on amperometric and optical transducers. Clearly the optimal starting point for all graduate students, postdoctoral and senior researchers, and technicians in academia, industry, and research establishments seeking rapid entry into the field of biosensors, Affinity Biosensors: Protocols and Techniques instantly becomes today's leading reference. Its step-by-step descriptions of various affinity biosensor techniques will allow both novices and experienced investigators alike successfully to apply these powerful new tools, and thus sharply enhance their laboratories' productivity.